Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004013.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Types of urethral catheters for management of short-term voiding problems in hospitalised adults

Abstract: The results suggest that the use of silver alloy indwelling catheters for catheterising hospitalised adults short-term reduces the risk of catheter acquired urinary tract infection. Further economic evaluation is required to confirm that the reduction of infection compensates for the increased cost of silver alloy catheters.Catheters impregnated with antibiotics are also beneficial in reducing bacteriuria in hospitalised adults catheterised for less than one week but the data were too few to draw conclusions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
3
17

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 38 publications
3
142
3
17
Order By: Relevance
“…The use of catheters impregnated with antibiotics for up to a week was effective in the reduction of bacteriuria, although this data was not very conclusive in confirming this same efficacy when the catheter was used for a prolonged period (21) . When a catheter impregnated with nitrofurazone was used, in comparison with a silicone catheter, there was a reduction in the incidence of bacteriuria and funguria (26) .…”
Section: Type Of Catheter Materialsmentioning
confidence: 83%
See 2 more Smart Citations
“…The use of catheters impregnated with antibiotics for up to a week was effective in the reduction of bacteriuria, although this data was not very conclusive in confirming this same efficacy when the catheter was used for a prolonged period (21) . When a catheter impregnated with nitrofurazone was used, in comparison with a silicone catheter, there was a reduction in the incidence of bacteriuria and funguria (26) .…”
Section: Type Of Catheter Materialsmentioning
confidence: 83%
“…The use of catheters impregnated with silver alloy for up to one week when compared to common catheters had a significant reduction in the incidence of asymptomatic bacteriuria. With more than one week of catheterization, the risk of asymptomatic bacteriuria continued reduced with the use of a silver alloy coated catheter (21)(22) . A reduction in UTI was also obtained when a hydrophilic coated catheter, rather than a plastic one, was used in patients carrying out self-catheterization (23) .…”
Section: Type Of Catheter Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic (minocycline, rifampicin, nitrofurantoin) impregnated catheters lowered the rate of asymptomatic bacteriuria compared to catheters without impregnation at less than one week but difference was not statistically significant at greater than one week, and the authors concluded that the data were too few to draw conclusions about long-term catheterization. [76] Silver alloy catheters significantly reduced the incidence of asymptomatic bacteriuria at less than one week of catheterization [76]. Beyond one week the estimated effect was smaller but the risk of asymptomatic bacteriuria was still less in the silver alloy group.…”
Section: Prevention Of Biofilm Formation In the Urinary Tractmentioning
confidence: 92%
“…Prophylaxis with Antimicrobial Agents.Systemic antibiotic drug therapy has been shown repeatedly in prospective and retrospective studies to prevent CA-bacteriuria,although the protective effect appears to be transient and development of antimicrobial resistance has been noted in some studies [8].Unfortunately,as many as 60% to 80% of hospitalized catheterized patients receive antimicrobials for variety of reasons, and not controlling for this important variable in the analyses of many intervention trials may explain why some interventions have not been shown to be effective in CA-bacteriuria [55].…”
Section: Avoidance Of Catheterizationmentioning
confidence: 99%